Co-development of a transitions in care bundle for patient transitions from the intensive care unit: a mixed-methods analysis of a stakeholder consensus meeting - Brianna K. Rosgen; Kara M. Plotnikoff; Karla D. Krewulak; Anmol Shahid; Laura Hernandez; Bonnie G. Sept; Jeanna Morrissey; Kristin Robertson; Nancy Fraser; Daniel J. Niven; Sharon E. Straus; Jeanna Parsons Leigh; et al. (BMC, 2022)
Abstract Background Intensive care unit (ICU) patients undergoing transitions in care are at increased risk of adverse events and gaps in medical care. We evaluated existing patient- and family-centered transitions in care tools and identified facilitators, barriers, and implementation considerations for the application of a transitions in care bundle in critically ill adults (i.e., a collection of evidence-based patient- and family-centred tools to improve outcomes during and after transitions from the intensive care unit [ICU] to hospital ward or community). Methods We conducted a concurrent mixed methods (quan + QUAL) study, including stakeholders with experience in ICU transitions in care (i.e., patient/family partners, researchers, decision-makers, providers, and other knowledge-users). First, participants scored existing transitions in care tools using the modified Appraisal of Guidelines, Research and Evaluation (AGREE-II) framework. Transitions in care tools were discussed by stakeholders and either accepted, accepted with modifications, or rejected if consensus was achieved (≥70% agreement). We summarized quantitative results using frequencies and medians. Second, we conducted a qualitative analysis of participant discussions using grounded theory principles to elicit factors influencing AGREE-II scores, and to identify barriers, facilitators, and implementation considerations for the application of a transitions in care bundle. Results Twenty-nine stakeholders attended. Of 18 transitions in care tools evaluated, seven (39%) tools were accepted with modifications, one (6%) tool was rejected, and consensus was not reached for ten (55%) tools. Qualitative analysis found that participants' AGREE-II rankings were influenced by: 1) language (e.g., inclusive, balance of jargon and lay language); 2) if the tool was comprehensive (i.e., could stand alone); 3) if the tool could be individualized for each patient; 4) impact to clinical workflow; and 5) how the tool was presented (e.g., brochure, video). Participants discussed implementation considerations for a patient- and family-centered transitions in care bundle: 1) delivery (e.g., tool format and timing); 2) continuity (e.g., follow-up after ICU discharge); and 3) continuous evaluation and improvement (e.g., frequency of tool use). Participants discussed existing facilitators (e.g., collaboration and co-design) and barriers (e.g., health system capacity) that would impact application of a transitions in care bundle. Conclusions Findings will inform future research to develop a transitions in care bundle for transitions from the ICU, co-designed with patients, families, providers, researchers, decision-makers, and knowledge-users.